Case report: Primary infection of conjunctival histoplasmosis mimicking a large conjunctival neoplasm in an immunosuppressed patient - Lam, Jonathan; Hussain, Rumana; Coupland, Sarah E.; Heimann, Heinrich (Frontiers in Medicine, 2024)
We report a rare case of a rapidly growing and large conjunctival histoplasmosis lesion in an immunosuppressed West African woman in her 80s, affecting her only eye. The patient had undergone a renal transplant and was on immunosuppressive medications. Additionally, she had previously been treated for presumed systemic histoplasmosis with itraconazole more than 5 years ago. Despite receiving previous treatment, she presented with a large conjunctival lesion, which was confirmed to be histoplasmosis after an excisional biopsy. The lesion was observed to grow over a 2-week period, causing significant visual impairment. Following a comprehensive systems review and investigation, the conjunctiva was identified as the sole site of infection. This case underscores the rarity of sight-threatening Histoplasma infections in the conjunctiva of an immunosuppressed individual. Conjunctival histoplasmosis lesions are rarely reported, with even fewer cases documented as primarily originating from this location.